Simvastatin alleviates experimental autoimmune encephalomyelitis through regulating the balance of Th17 and Treg in mice - Xu, Dongsheng; Wang, Manxia; Wang, Lijuan (Allergologia et Immunopathologia, 2024)
The aim of this study was to elucidate the therapeutic effect of simvastatin on experimental autoimmune encephalomyelitis (EAE) by regulating the balance between Th17 and Treg cells in mice. C57BL/6 mice were randomly divided into four groups: normal group, EAE group, simvastatin (2 and 10 mg/kg) group, and AG490 group (with AG490 serving as the positive control). Neurological function scores of mice were assessed daily. The four groups received treatments of normal saline, normal saline, and simvastatin (2 and 10 mg/kg), respectively. In the AG490 group, mice were injected intraperitoneally with AG490 (1 mg) every other day, and treatment was halted after 3 weeks. The spinal cord was stained with hematoxylin and eosin (H&E), and immunohistochemical staining for retinoic acid receptor-related orphan receptor γ(RORγ) and Foxp3 (Foxp3) was performed. Spleen samples were taken for Th17 and Treg analysis using flow cytometry. The levels of interleukin-17 and transforming growth factor-β (TGF-β) were detected using enzyme-linked immunosorbent assay (ELISA). In the simvastatin and AG490 groups, recovery from neurological impairment was earlier compared to the EAE group, and the symptoms were notably improved. Both simvastatin and AG490 reduced focal inflammation, decreased RORγ-positive cell infiltration, and significantly increased the number of FOXP3-positive cells. The number of Th17 cells and the level of IL-17 in the spleen were decreased in the simvastatin and AG490 treatment groups, while the number of Treg cells and TGF-β levels were significantly increased across all treatment groups. Simvastatin exhibits anti-inflammatory and immunomodulatory effects, potentially alleviating symptoms of neurological dysfunction of EAE. Regulating the balance between Th17 and Treg may represent a therapeutic mechanism for simvastatin in treating EAE.